Nur Syuhada, recipient of Anugerah Prihatin Komuniti Puspanita, active in association - Shalfarina, Shahriman (2022)
Kuantan, 18 March 2022 – Being active in co-curricular activities and associations did not prevent Nur Syuhadah Abu, 25, from obtaining a Cumulative Grade Point Average (GPA) of 3.75 and thus obtaining a First Class Degree during her study at Universiti Malaysia Pahang (UMP).